Transparency and Monetary Policy with Imperfect Common Knowledge - Roca, Mauro (Washington, D.C. : International Monetary Fund, 2010)
Is it desirable that central banks be more transparent in the communication of sensible information when agents have diverse private information? In practice, there exists some consensus about the benefits of acting in this way. However, other studies warn that increasing the precision of public information may raise the volatility of some aggregate variables - in particular, the price level - due to the disproportionate influence that it exerts on agents' decisions, and that this, in turn, will have negative effects on welfare. This paper studies the welfare effects of varying levels of transparency in a model of price-setting under monopolistic competition and imperfect common knowledge. Our results indicate that more precise public information never leads to a reduction of welfare in this framework. We find that the beneficial effects of decreased imperfect common knowledge due to a more precise common signal always compensates the potential rise in aggregate volatility. Moreover, we show that, in contrast to what has previously been assumed, the variability of the aggregate price level has no detrimental welfare effects in this model.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United Kingdom